Retention and attrition of adult patients on antiretroviral therapy in Bojanala District, North West Province, South Africa, 2009–2014 - Pilusa, Mapula Cathrine (My University, 2020)
Introduction: Globally, the HIV/AIDS pandemic continues to be a major public health problem. Despite efforts in Low and Middle Income Countries (LMICs) such as Kenya, Malawi, Eritrea, Botswana and South Africa to manage the public health burden of HIV/AIDS through Anti-Retroviral Treatment (ART) programmes; some challenges have been recorded. LMICs that have adopted ART programmes to treat HIV/AIDS have been lauded as successful in improving the health outcomes of people living with HIV/AIDS (PLWHIV). Consequently, while ART has been widely expanded in the public health facilities in LMICs and South Africa in particular, the majority of ART programmes are affected by low retention and attrition. The aim of this study was to explore the factors that influence retention and attrition of adults who started ART between 2009 to 2014 in Tlhabane Community Health Care (CHC), Bojanala District, North West Province in South Africa. Methods: A retrospective review of 1000 electronic clinical records was conducted in Tlhabane CHC in 2017. The study included electronic records of patients who started ART between 2009 to 2014 and were followed up for 60 months. Stata (version14) was used to analyse data. Descriptive statistics were used to summarise patient’s demographics and baseline characteristics. Kaplan-Meier curves were used to graphically assess retention proportions. Univariate and multivariate Cox proportional hazard models were used to determine factors associated with attrition. Results: The key factors associated with attrition in the study sample of adult patients aged 18 –49 years, who started ART in Tlhabane CHC between 2009-2014 were identified, 648 (64.8%) were female and 352 (35.2%) were male. Retention proportions declined over time from 92.9% (95% CI 91.1-94.3%),88.5% (95% CI 86.3 -90.3%), 82.4% (95% CI 79.8 -84.6%), 77.1% (95% CI 74.3 -79.7%), 72.1% (95% CI 69.0 -74.9%) and 63.0% (95% CI 59.5-66.3%) at 6, 12, 24, 36, 48 and 60 months respectively. Females were more retained as compared to their male counterparts. In the univariates analysis, age group of 36-49, patients with baseline CD4 count of 101-200cells/uL and those on D4T/3TC/EFV treatment regimen were significantly retained in care. Factors associated with attrition in Tlhabane CHC were WHO clinical stage II and IV, being a male patient and having an unsuppressed viral load (VL>1000copies/uL) in the cohort. The multivariate analysis showed that the number of missed appointment visits were associated with increased risk of attrition. Conclusion: The findings of this study highlighted the key factors associated with attrition in the sample of adult patients aged 18 –49, who started ART in Tlhabane CHC between 2009 -2014. More sustainable interventions to reverse the ongoing trend of attrition in Tlhabane CHC might be beyond this study, although it suggested a number of recommendations. Among these are to offer ongoing intensive adherence counselling to asymptomatic patients, those with WHO clinical stage II and the virally unsuppressed to ensure commitment to lifelong treatment in Tlhabane CHC. Early ART initiation should be prioritized to patients in order to prevent advanced disease and poor prognosis while on treatment. Pharmacovigilance monitoring, education on the side effects of ARVs and encouraging patients to have treatment supporters is critical in order to prevent poor adherence and LTFU related to adverse drug events. Offering male-friendly services to motivate them to utilize the facility without fear of stigma and prejudice is highly recommended. Clinicians can minimize missing of clinic appointments by involving patients when scheduling their appointments. Stigma mitigation through community dialogues, campaigns and awareness will make patients to utilize services within their geographical area, thereby ensuring more patients’ retention and reducing attrition
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Public Health in the field of Health Systems and Policy Research, 2020